Legami di coppia e affettività. Dall’amore romantico alla relazione pura - Biancheri, Rita (SocietàMutamentoPolitica, 2012)
In this paper we examine the changes that have characterized bonds between couples and affectivity, through the contributions of classical as well as contemporary sociologists. Starting from the family as a social institution, we go on to an examination of transformations in intimacy and in relations of negotiation, with an eye towards interdisciplinary contributions.